Preliminary report on the status and host plant utilization by the Black Coffee Twig Borer, Xylosandrus compactus (Eichhoff) (Coleoptera: Curculionidae) in Uganda - Kagezi, G.H.; Kucel, P.; Mukasa, D.; Asten, Piet J.A. van; Musoli, P.C.; Kangire, A. (Association for Science and Information on Coffee, 2012)
The Black Coffee Twig Borer, Xyalosandrus compactus (Eichhoff) is a new but rapidly spreading pest of coffee and other plant species. However, knowledge of its pest status, damage and host plant species utilization in Uganda is still limited. To ascertain its spread and impact, a survey was conducted on 250 farms in 25 districts in the 5 major coffee growing regions of Uganda. At farm level, 12 coffee trees were randomly sampled along a diagonal transect and assessed for X. compactus infestation. In addition, host plant utilization by the pest was determined through farmers’ interviews and direct search by researchers. Our data show that the pest is present in all the 5 districts (100%) sampled in central region viz:- Mukono, Luwero, Mityana, Mubende and Mpigi, and at least 50% of the districts in southwestern viz:- Bundibugyo, Kasese and Rubirizi. However, the beetle was not observed in northwestern (West Nile), northern and part of eastern (Mt. Elgon) regions. X. compactus prevalence (percentage of infested farms), incidence (percentage of infested trees) and damage (percentage of infested primary branches) were 58.1, 34.0 and 3.8% respectively in the central region whereas, 22.1, 7.7 and 0.8% respectively in the southwestern region. At district level, the highest prevalence (100%) was observed in Mukono and Luwero then Bundibugyo (62.5%), Mityana (50.0%), Rubirizi (40%) and Kasese (30%). Similarly, high incidence rates of 91.7, 73.3 and 44.8% were observed in Mukono, Luwero and Bundibugyo respectively. Likewise, high damage rates of 13.6, 5.2 and 4.8% were observed in Mukono, Luwero and Bundibugyo districts respectively. Further, our study identified and documented more than 30 plant species in 17 families as potential hosts for X. compactus. These include important commercial and food crops, forest, fruit and shade trees and shrubs. In conclusion, this study confirms earlier surveys and reports that the black coffee twig borer is fast and rapidly spreading away from its initial occurrence (southwestern Uganda) and epicenter (central Uganda) to new infestation areas, posing a big threat to coffee production in the country. Therefore, there is an urgent need to put in place comprehensive mitigation measures in order to prevent the pest from spreading to new areas and also to minimize its impact on coffee production within the already affected areas.